Utilization and prospect of purification technologies in natural proteins, peptides and recombinant proteins - Eskandari, Azadeh; Thean, Chor Leow; Abdul Rahman, Mohd Basyaruddin; Oslan, Siti Nurbaya (Springer, 2024)
Protein, being a fundamental biological macromolecule, assumes a critical function in various vital activities of cellular growth, heredity, reproduction, and other biological processes. Moreover, the utilization of recombinant proteins is extensive in the advancement of pharmaceutical materials, enzyme industrial implementation, and fundamental proteomics investigation. Effective purification methods are necessary for the production of recombinant proteins as well as natural proteins and peptides to ensure their efficient production. Various methods have been developed to improve protein purification, incorporating the recent advancements in protein separation technology. This review is focused on the sophisticated approach to the purification techniques of protein, peptide, and recombinant protein. The system known as the multi-column plate adapter (MCPA) proves to be highly cost-effective in the field of protein purification methods. The assessment has determined that the method of employing an aqueous two-phase system (ATPS) is an economically sound, and highly efficient approach in protein purification. Thus, the ATPS might represent a feasible approach to single-stage purification, deviating from the complex chromatography procedure. The chromatography strategies have been improved for the purification of peptides including batch liquid, continuous and semi-continuous chromatography. In the realm of recombinant protein purification, affinity purification presents several advantages compared to alternative methods. To produce, identify, and purify recombinant proteins from their host systems in large quantities with high efficiency, affinity strategies—particularly fusion strategies—have been developed. Hence, the purpose of this review is to implement the various purification technologies, their potential employments, fundamentals, advantages, and limitations.